Simultaneous 3-/4-Hydroxybenzoates Biodegradation and Arsenite Oxidation by Hydrogenophaga sp. H7 - Fan, Xia; Nie, Li; Shi, Kaixiang; Wang, Qian; Xia, Xian; Wang, Gejiao (Frontiers in Microbiology, 2019)
Abstract Aromatic compounds and arsenic (As) often coexist in the environment. As(III)-oxidizing bacteria can oxidize the more toxic As(III) into the less toxic As(V), and As(V) is easily removed. Microorganisms with the ability to degrade aromatic compounds and oxidize arsenite [As(III)] may have strong potential to remediate co-contaminated water. In this study, a Gram-negative bacterium Hydrogenophaga sp. H7 was shown to simultaneously degrade 3-hydroxybenzoate (3-HBA) or 4-hydroxybenzoate (4-HBA) (3-/4-HBA) and oxidize arsenite [As(III)] to arsenate [As(V)] during culture. Notably, the addition of As(III) enhanced the degradation rates of 3-/4-HBA, while the addition of 3-/4-HBA resulted in a slight delay in As(III) oxidation. Use of a 1% bacterial culture in combination with FeCl3 could completely degrade 250 mg/L 3-HBA or 4-HBA and remove 400 μM As(III) from simulated lake water within 28 h. Genomic analysis revealed the presence of As(III) oxidation/resistance genes and two putative 3-/4-HBA degradation pathways (the protocatechuate 4,5 dioxygenase degradation pathway and the catechol 2,3 dioxygenase degradation pathway). Comparative proteomics suggested that strain H7 degraded 4-HBA via the protocatechuate 4,5 dioxygenase degradation pathway in the absence of As(III); however, 4-HBA could be degraded via the catechol 2,3 dioxygenase degradation pathway in the presence of As(III). In the presence of As(III), more NADH was produced by the catechol 2,3 dioxygenase degradation pathway and/or by As(III) oxidation, which explained the enhancement of bacterial 4-HBA degradation in the presence of As(III). In addition, the key gene dmpB, which encodes catechol 2,3 dioxygenase in the catechol 2,3 dioxygenase degradation pathway, was knocked out, which resulted in the disappearance of As(III)-enhanced bacterial 4-HBA degradation from the dmpB mutant strain, which further confirmed that As(III) enhancement of 4-HBA degradation was due to the utilization of the catechol 2,3 dioxygenase pathway. These discoveries indicate that Hydrogenophaga sp. H7 has promise for the application to the removal of aromatic compounds and As co-contamination and reveal the relationship between As oxidation and aromatic compound degradation.